Imposition of Ex-Wife's Post-Divorce Livelihoods: A Socio-Legal Overview - Melany Fauzia Jusuf (Universitas Negeri Gorontalo, 2020)
Abstract: This study aims to determine how the fulfillment of the rights of the ex-wife in obtaining the burden of living after the divorce decision. This type of research is a sociological jurisprudence based on the jurisprudence school. This research is based on normative law (statutory regulations), but does not examine the system of norms that work in society. The analysis used in this study is descriptive data analysis using a qualitative approach to secondary legal materials and primary legal materials. The description includes the content and structure of positive law and Islamic law, which is an activity carried out by the author to analyze the determination. The results of this study indicate that the fulfillment of the burden of living after the divorce decision by the ex-husband to the ex-wife in divorce cases, in its implementation has not run optimally in all divorce cases accompanied by the burden of living, although this has been based on a judge's decision which has permanent legal force. Fulfillment of the burden of living after the divorce decision in his position is largely determined by the good faith of the ex-husband in fulfilling the responsibility of burdening the living voluntarily by the contents of the court's decision as to the party who is burdened with a living. So that to realize the maximum post-divorce burden of living in all divorce cases with the qualification of the burden, in this case, it is important to immediately give birth to the concept of legal reform in fulfilling the payment of living by guaranteeing the property of the ex-husband by including the element of guaranteeing the property of the ex-husband in the the decision handed down and presenting a mechanism for executing for free or for free.